(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Barangay Health Care Center is a community-based facility that offers first aid, child health care, and other basic services to Barangay residents. This research aims to determine the level of satisfaction with the health care service provided by Barangay Gulod Quezon City. The result shows the percentage distribution of the respondents. The Demographic profile Table 1 shows age 18-59 50% and 60 above 50% with a total of 100%, while Gender Table 2 shows the total number percentages of male respondents (33%) and female respondents (67%). Reliability Table 3 shows a composite mean of non-senior 3.35 and senior 3.52, with both verbal interpretations strongly agreeing. Tangibles Table 4 shows a composite mean of non-seniors 3.44 with verbal interpretation strongly agree, and seniors 2.68 with verbal interpretation agree. Vaccines and Medicine Table 5 composite mean of non-senior 2.53 with verbal interpretation agree and senior 2.8 with verbal interpretation agree, Priority Lane Table 6 shows a composite mean of non-senior 2.27 with verbal interpretation disagree and senior 3.24 with verbal interpretation agree, Records Table 7 shows a composite mean non- senior 2.57 with verbal interpretation agree and senior with verbal interpretation 2.55 agree, Responsiveness Table 8 shows a composite mean non-senior 3 with verbal interpretation agree and senior 3.19 with verbal interpretation agree, Table 9 shows the significant difference between the assessments of non-senior and senior respondents in terms of cited variables. It reveals that the reliability, vaccine and medicine, records, and responsiveness have no significant differences between the two groups; however, the tangibles and priority lane are significant for both respondents. Table 10 shows the problem and solution of the researcher’s administrator. The researchers recommended an improvement plan to address the concerns highlighted in the study and improve the healthcare center's service quality. These include conducting regular patient feedback surveys to identify areas for improvement and measure the success of implemented improvements, investing in staff training, and upgrading technology to improve the efficiency and effectiveness of operations.